SEM-EDS and biomechanical evaluation of implants with different surface treatments: an initial study - Tavares, Hewerson Santos; Faeda, Rafael Silveira; Guastaldi, Antônio Carlos; Semeghini Guastaldi, Fernando Pozzi; Oliveira, Nilson T.C.; Marcantônio Jr., Élcio (Journal of Osseointegration, 2009)
Aim Alterations in implant surfaces can affect periimplant bone formation and shorten the healing time. The goal of the present study was a comparative scanning electron microscopy (SEM)/energy dispersive spectrometry (EDS) and biomechanical evaluation of implants subjected to different surface treatments. Materials and Methods Four implant surfaces were analyzed in the present study: machined commercial implants (TU); porous-surfaced commercial implants blasted with Al2O3 microspheres and acid-etched (TJA); laser beam-irradiated experimental implants (Laser) and laser beam-irradiated experimental implants with hydroxyapatite coating (HA). One sample for each surface underwent pre-surgery SEM / EDS analysis. Thirty- two implants (8 for each surface treatment) were then inserted into the tibia of 4 rabbits. After 8 weeks, the animals were euthanized and the implants retrieved by reverse torque and processed for post-surgery SEM / EDS analysis. Results HA implants presented higher removal torque values when compared to Laser, TJA and TU groups. Post-surgery SEM micrographs clearly showed bone formation on all the examined surfaces; however, in the TU group bone covered only some areas of the implant surface, while in TJA, Laser and HA groups the entire implant surfaces were overlaid by newly formed bone. EDS analysis supported the results obtained by SEM and removal torque, showing that concentration of Ca and P increased from TU to TJA, Laser and HA implants. Conclusions Implants with surfaces modified by laser beam with or without apatite coating showed more promising results.